General characteristics of tidal currents in the entrance of Khor Abdullah, northwest of Arabian Gulf - Ali Abdulridha Lafta (Oceanologia, 2023)
The general characteristics of tidal currents in the entrance of the Khor Abdullah at Iraq marine water, located at the northwest tip of the Arabian Gulf, were studied based on realistic current measurements. The velocity measurements used in this study extended to about one year, which was never previously available in this vital region of the Arabian Gulf. The results illustrated that this area is characterized by strong currents exceeding 1 m/s during both ebb and flood tides, driven by local water level variations. The maximum currents recorded during the study period were 1.65 and 1.36 m/s at the ebb and flood tides, respectively. Additionally, the monthly averages of ebb currents are higher than those of flood currents. The harmonic analysis results revealed that the tidal effect explained approximately 98% of the variation in water currents, with the remaining percentage due to residual currents. Among the 35 tidal components used in harmonic analysis, the M2 component was the main contributor to tidal currents variation in the area, followed by S2, K1, N2, and O1. The residual current seems to have a low effect on the currents variations in the area, with maximum values not exceeding 0.0677 and 0.058 m/s during the ebb and flood tides, respectively. The results obtained give a general view of the tidal current behavior and could be beneficial for several aspects of marine and coastal engineering as well as shipping and navigation activities in this region.